Study to Probe Subsistence of Host-Guest Inclusion Complexes of α and β-Cyclodextrins with Biologically Potent Drugs for Safety Regulatory Dischargement - Biplab Rajbanshi (Nature Portfolio, 2018)
Abstract Host-guest interaction of two significant drugs, phenylephrine hydrochloride and synephrine with α and β-cyclodextrins were studied systematically. Initially two simple but reliable physicochemical techniques namely conductance and surface tension were employed to find out saturation concentration for the inclusion and its stoichiometry. The obtained 1:1 stoichiometry was further confirmed by two spectrometric methods, UV-Vis study and spectrofluorimetry. Significant shifts in IR stretching frequency also support the inclusion process. Relative stabilities of the inclusion complexes were established by the association constants obtained from UV-Vis spectroscopic measurements, program based mathematical calculation of conductivity data. Calculations of the thermodynamic parameters dictates thermodynamic feasibility of the inclusion process. Spectrofluorometric measurement scaffolds the UV-Vis spectroscopic measurement validating stability of the ICs once again. Mass spectroscopic measurement gives the molecular ion peaks corresponding to the inclusion complex of 1:1 molar ratio of host and guest molecules. The mechanism of inclusion was drawn by 1H-NMR and 2D ROESY spectroscopic analysis. Surface texture of the inclusion complexes was studied by SEM. Finally, the cytotoxic activities of the inclusion complexes were analyzed and found, Cell viability also balances for non-toxic behavior of the ICs. Moreover, all the studies reveal the formation of inclusion complexes of two ephedra free, alternatively emerging drugs (after their banned product having ephedra) SNP, PEH with α and β-CD which enriches the drug delivery system with their regulatory release without any chemical modification.